Composition, diversity and structure of woody species in temperate forests of Monte Grande, Sierra Fría, Aguascalientes, Mexico - Martínez-Calderón, Víctor Manuel; Sosa-Ramírez, Joaquín; Siqueiros-Delgado, María Elena; Díaz-Núñez, Vicente (Instituto de Ecología, A.C., 2021)
Background and Aims: Within the Natural Protected Area Sierra Fría (ANPSF), Aguascalientes, Mexico, some studies have been carried out on the composition, diversity and dynamics of temperate forests in lowlands; in this work we studied Monte Grande, its highest area. The aim of this study was to characterize the composition, diversity and structure of the woody species communities in the temperate forests of Monte Grande, within the ANPSF. Methods: Individuals with a basal diameter ≥5 cm were measured in 32 transects of 300 m2. A grouping by cluster analysis and subsequently Kruskal-Wallis and ANOVA tests were performed to find differences between plant associations. The analyzed data included density, basal area, height, relative importance value, richness and effective number of species. Key results: Twenty-six woody species (nine genera and eight families) were identified in five associations: Quercus sideroxyla-Quercus rugosa oak forest, Quercus potosina-Arctostaphylos pungens oak forest, Quercus-Pinus mixed forest, Juniperus-Quercus mixed forest and Juniperus forest. The Q. sideroxyla-Q. rugosa forest had the largest basal area value (53 m2/ha), and the Quercus-Pinus forest had the highest density (2200 ind/ha). The effective number of species varied between 1.50-4.031D 1.27-3.242D. The abundance of A. pungens and J. deppeana, considered pioneers, was high. Conclusions: The structure and diversity of the associations presented differences due to their composition, the conditions in which the associations develop, and the management history of Monte Grande. The generated information provides a reference frame for decision making in relation to the conservation and use of the forests of the region.